2013
DOI: 10.1002/mma.2907
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of a self‐cycling fermentation model with state‐dependent impulse times

Abstract: Artículo de publicación ISIA self-cycling fermenter is a batch fermenter subject to recurrent emptyings of liquid volume followed by the refillingwith new fresh substrate. This article constructs amodified model of self-cycling fermenter, which is described by an impulsive differential equation at impulse-dependent times, which have been recently introduced. The main result is a set of conditions depending of the fraction of removed volume, the concentration of new substrate introduced, and the maximal len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Let u ± k = (s 1 (t ± k ), s 2 (t ± k )). By (6), the trajectory of (s 1 (t), s 2 (t)), t ∈ (t k , t k+1 ), is a line segment with slope R 21 and endpoints u + k and u − k+1 . The conditions for impulses to occur are given in (2).…”
Section: Analysis Of the Full Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Let u ± k = (s 1 (t ± k ), s 2 (t ± k )). By (6), the trajectory of (s 1 (t), s 2 (t)), t ∈ (t k , t k+1 ), is a line segment with slope R 21 and endpoints u + k and u − k+1 . The conditions for impulses to occur are given in (2).…”
Section: Analysis Of the Full Systemmentioning
confidence: 99%
“…Fan and Wolkowicz [7] extended this model to include the possibility that the resource is limiting at large concentrations. Córdova-Lepe, Del Valle, and Robledo [6] also modeled single species growth in the SCF process, but used impulse dependent impulse times instead of the state dependent impulses used by the other models. For references on the theory of impulsive differential equations, see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our paper, we will use the notation and some facts from this monograph. The study of real-life problems with statedependent impulse effects can be found, for example, in [2,6,9].…”
Section: Introductionmentioning
confidence: 99%